A primer for calculus - Holder, Leonard Irvin (Belmont, California : Wadsworth Publishing Company, 1987)
This new edition has the same objective as its predecessors: to provide background material for the study of calculus in an informal yet mathematically sound style that is appropriate for students at this level.
1. Basic algebraic concepts -- 2. Equations and inequalities of the first and second degree -- 3. Functions and graphs -- 4. Linear and quadratic functions -- 5. Polynomial functions of higher degree -- 6. Exponential and logarithmic functions -- 7. Introduction to trigonometric functions -- 8. Analytical trigonometry -- 9. Systems of equations and inequalities -- 10. Further aids to graphing -- 11. The conic sections -- 12. Sequences and series.
Includes index.
Keywords: MATHEMATICS